Intraindividual variance of lower limb rotation in patients with bilateral knee osteoarthritis - Zheng, Xin; Wang, Yang-yu-fan; Jin, Wang-yi; Huang, Chao-ran; Yan, Zi-wen; Peng, Da-lin; Zhou, Shen; Guo, Kai-jin; Pan, Sheng (Frontiers in Surgery, 2023)
Purpose: To determine the side-to-side difference in intra-individual rotation alignment of patients with bilateral varus-type knee osteoarthritis (OA) and compare it with control subjects. Methods: This retrospective study enrolled 60 patients with bilateral varus-type knee OA and 50 control subjects. All cases underwent bilateral lower limb CT angiography. Bilateral femoral and tibial rotation alignment were measured and the overall lower limb rotation was calculated by two different methods. Method 1 was calculated by subtracting angle of the femoral torsion from the tibial torsion and method 2 was determined by relative rotation of the femoral neck angle to bimalleolar angle. The intra‑individual variance and differences between the two groups were analyzed. Results: Both OA and control samples showed significant differences between right and left for all measurements. Femoral torsion for control group was 10.4±5.5°, tibial torsion was -22.1±6.1°, overall leg rotation by method 1 was -15.6±7.2° and method 2 was -11.7±8.2°. Femoral torsion, tibial torsion, method 1 and method 2 in the patients with OA were 8.2±6.3°, -18.6±4.1°, -14.9±7.9° and -10.4±7.6° respectively. Patients with OA showed a more pronounced retroversion in the femur (p=0.008) and more internal rotation in the tibia (p<0.001). No statistical significance of both methods was found between the two groups. Patients with OA had a greater median side-to-side absolute difference in all measurements, though the differences of both two methods of overall lower limb rotation were not statistically significant. Conclusions: The discrepancy of side-to-side differences of bilateral lower limb rotation ought to be noticed with caution in diagnosing and treating rotational deformities of lower limb, especially for patients with bilateral knee OA .